Combined repetitive transcranial magnetic stimulation and gut microbiota modulation through the gut–brain axis for prevention and treatment of autism spectrum disorder - Feng, Pengya; Zhang, Yangyang; Zhao, Yonghong; Zhao, Pengju; Li, Enyao (Frontiers in Immunology, 2024)
Autism spectrum disorder (ASD) encompasses a range of neurodevelopmental conditions characterized by enduring impairments in social communication and interaction together with restricted repetitive behaviors, interests, and activities. No targeted pharmacological or physical interventions are currently available for ASD. However, emerging evidence has indicated a potential association between the development of ASD and dysregulation of the gut-brain axis. Repetitive transcranial magnetic stimulation (rTMS), a noninvasive diagnostic and therapeutic approach, has demonstrated positive outcomes in diverse psychiatric disorders; however, its efficacy in treating ASD and its accompanying gastrointestinal effects, particularly the effects on the gut–brain axis, remain unclear. Hence, this review aimed to thoroughly examine the existing research on the application of rTMS in the treatment of ASD. Additionally, the review explored the interplay between rTMS and the gut microbiota in children with ASD, focusing on the gut-brain axis. Furthermore, the review delved into the integration of rTMS and gut microbiota modulation as a targeted approach for ASD treatment based on recent literature. This review emphasizes the potential synergistic effects of rTMS and gut microbiota interventions, describes the underlying mechanisms, and proposes a potential therapeutic strategy for specific subsets of individuals with ASD.